The king's ransom [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Gabriela Rose novel., 2025)
Gabriela Rose, recovery agent extraordinaire, can find just about anything. Too bad she can't seem to lose her gorgeous-but-infuriating ex-husband Rafer Jones. And now he needs her help. His cousin, Harley, is in trouble - big trouble. As the president of a too-big-to-fail bank, he invested an astronomical amount of money in insuring some of the world₂s most priceless artifacts at the urging of his board. It seemed like a low-risk, high-reward business move, so he jumped in with both feet. But recently, these insured pieces started going missing and worse, there's no paper trail of Harley being directed to make these risky investments. Unless the artwork can be recovered soon, it looks like Harley is going to be heading to jail as the fall guy for an ingenious crime. Gabriela knows what she must do: travel around the world with Rafer to find the missing works of art, keep Harley out of jail, and save both his skin and his bank. Along the way, she₂ll encounter corruption, threats, murder, mysterious dark forces behind a global conspiracy to destroy the world₂s wealth, and a nefarious villain who will stop at nothing to bring the world to the brink of ruin.